DEPRESSION AS A SERIOUS HUMAN DILEMMA IN THE NOVEL "MOTH SMOKE" BY MOHSIN HAMID - Ayaz, Maria; Numan, Muhammad (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Depression is a severe dilemma in our society, a sense of bleakness, confusion, and overthinking. Due to this dilemma, many unruly arise in human life, and humans face many consequences; many people die due to this dilemma in the world. Nobody understands the seriousness of this dilemma, and no one even understands the psyche of depressed people, and cannot understand their feelings and emotions and consider them as a psycho person. The primary purpose of this research is to show the severity of this dilemma that how this dilemma brings disasters in human life, ruins the personality of a normal person, and makes them psycho in the eyes of society. We must highlight the seriousness of this dilemma to achieve better results and peace of mind and create a better society. So, this research explores the seriousness of this dilemma that destroys many people, and their lives become a sea of sadness, tension, and empty feelings. This study seeks to answer research questions that how does the severe dilemma of depression affects the people of the world. The goal is to analyze the demographics of this dilemma of depression and determine how we can get relief from this dilemma or how we can overcome the destruction of this dilemma.